Horizontal transfers of Mariner transposons between mammals and insects - Oliveira, Sarah G. [UNESP]; Bao, Weidong; Martins, Cesar [UNESP]; Jurka, Jerzy (Biomed Central Ltd., 2012)
Background: Active transposable elements (TEs) can be passed between genomes of different species by horizontal transfer (HT). This may help them to avoid vertical extinction due to elimination by natural selection or silencing. HT is relatively frequent within eukaryotic taxa, but rare between distant species.Findings: Closely related Mariner-type DNA transposon families, collectively named as Mariner-1_Tbel families, are present in the genomes of two ants and two mammalian genomes. Consensus sequences of the four families show pairwise identities greater than 95%. In addition, mammalian Mariner1_BT family shows a close evolutionary relationship with some insect Mariner families. Mammalian Mariner1_BT type sequences are present only in species from three groups including ruminants, tooth whales (Odontoceti), and New World leaf-nosed bats (Phyllostomidae).Conclusions: Horizontal transfer accounts for the presence of Mariner_Tbel and Mariner1_BT families in mammals. Mariner_Tbel family was introduced into hedgehog and tree shrew genomes approximately 100 to 69 million years ago (MYA). Most likely, these TE families were transferred from insects to mammals, but details of the transfer remain unknown.
Keywords: DNA transposon; Genome evolution; Horizontal transfer; Mariner